2020
DOI: 10.3389/fpls.2020.583539
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma Counteracts the Challenge of Phytophthora nicotianae Infections on Tomato by Modulating Plant Defense Mechanisms and the Expression of Crinkler, Necrosis-Inducing Phytophthora Protein 1, and Cellulose-Binding Elicitor Lectin Pathogenic Effectors

Abstract: Decoding the mechanisms of plant defense against plant pathogens in a scenario where antagonistic activity and the plant growth-promoting effects of useful organisms intervene simultaneously is a new frontier of plant pathology. Here, we demonstrated that (i) two selected strains of Trichoderma asperellum and Trichoderma atroviride promoted tomato ( Solanum lycopersicum ) growth and reduced the severity of disease caused by the oomycete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 86 publications
(115 reference statements)
2
43
1
1
Order By: Relevance
“…The current study indicated that UBQ was the overall most stable reference gene for P. radiata that was infected with F. circinatum or similar necrotrophic fungi. This evidence was congruent with the results of other research aiming to provide validation of reference genes on plants under biotic and abiotic stress situations [46,[49][50][51]. Therefore, UBQ was used for normalizing qRT-PCR results.…”
Section: Housekeeping Gene Selectionsupporting
confidence: 87%
See 1 more Smart Citation
“…The current study indicated that UBQ was the overall most stable reference gene for P. radiata that was infected with F. circinatum or similar necrotrophic fungi. This evidence was congruent with the results of other research aiming to provide validation of reference genes on plants under biotic and abiotic stress situations [46,[49][50][51]. Therefore, UBQ was used for normalizing qRT-PCR results.…”
Section: Housekeeping Gene Selectionsupporting
confidence: 87%
“…The study of gene expression was expected to be more effective than symptom severity to get a better insight into the response of the plant to multiple infections. It is well known that in plants, the infection by a pathogen triggers the activation of the main resistance mechanism, the systemic acquired resistance (SAR), which provides long-term resistance throughout the plant to subsequent infection by different pathogens [51]. This kind of resistance is correlated with the synthesis of pathogenesis-related (PR) proteins, which, in turn, is mediated by the up-regulation of genes encoding enzymes involved in the biosynthesis of salicylic acid (SA) [68].…”
Section: Discussionmentioning
confidence: 99%
“…The colonization of rhizosphere microorganisms in plant roots plays an important role in plant nutrition, competition and disease resistance [ 44 ]. This symbiotic relationship could mildly and effectively activate the plant immune response locally or systemically, thus plants respond more effectively to the stresses of potential biotic and abiotic factors [ 45 , 46 ]. Moreover, the relatively poor biocontrol effect observed in previous studies was usually associated with the failure of the colonization of inoculated biocontrol bacteria in the rhizosphere [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, different categories of biotic and abiotic stressors and biostimulants can trigger and modulate the plant immune response ( Khan et al, 2009 ; Deliopoulos et al, 2010 ; Puglisi et al, 2012 ; Calvo et al, 2014 ; du Jardin, 2015 ; La Spada et al, 2020 , 2021 ; Stracquadanio et al, 2021 ). The effectiveness of seaweed extracts and inorganic salts in eliciting natural plant defense mechanisms for the control of fungal diseases has been widely investigated ( Khan et al, 2009 ; Calvo et al, 2014 ; du Jardin, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Elicitor perception triggers various signaling pathways followed by the synthesis of further signal molecules, such as salicylic acid, jasmonic acid, and ethylene, which are in turn activators of the synthesis of defense metabolites in the plants ( Cluzet et al, 2004 ). An important category of induced plant defense metabolites is represented by pathogenesis-related (PR) proteins; among these, the PR-2 family enzyme β-1,3-glucanase can degrade the β-1,3-glucan, which is one of the main constituents of the fungal cell wall ( Youssef et al, 2014 ; La Spada et al, 2020 ). Another family of PR-proteins playing a key role in several metabolic responses in plant defense processes are plant peroxidases; they are involved in the formation of auxin metabolism, lignin, and suberin, cross-linking of cell wall components, the synthesis of phytoalexin, and the metabolism of reactive oxygen species (ROS) and reactive nitrogen species (RNS; Almagro et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%